2019
DOI: 10.1186/s12935-019-0947-2
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Translation Initiation Factor 4 Gamma 1 (EIF4G1): a target for cancer therapeutic intervention?

Abstract: Background Cap-dependent mRNA translation is essential for the translation of key oncogenic proteins at optimal levels and is highly regulated by the rate limiting, initiation step in protein synthesis. Eukaryotic Translation Initiation Factor 4 Gamma 1 (EIF4G1) serves as a scaffold for assembly of cap-dependent translation components in EIF4F complex formation. In the current study, we analyzed the role and expression of EIF4G1 in Pan human cancer panels through various approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
(47 reference statements)
2
24
0
Order By: Relevance
“…Thus, EIF4G1 acts as an oncoprotein [28] and represents an interesting CDG for further investigation as a possible therapeutic target for MPM. These findings corroborate recent work carried out by Jaiswal et al [29] on several types of cancers, including MPM. The authors showed that the overexpression of EIF4G1 was associated with a bad prognosis, leading them to conclude that EIF4G1 could be a novel potential target for therapeutic interventions [29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, EIF4G1 acts as an oncoprotein [28] and represents an interesting CDG for further investigation as a possible therapeutic target for MPM. These findings corroborate recent work carried out by Jaiswal et al [29] on several types of cancers, including MPM. The authors showed that the overexpression of EIF4G1 was associated with a bad prognosis, leading them to conclude that EIF4G1 could be a novel potential target for therapeutic interventions [29].…”
Section: Discussionsupporting
confidence: 93%
“…These findings corroborate recent work carried out by Jaiswal et al [29] on several types of cancers, including MPM. The authors showed that the overexpression of EIF4G1 was associated with a bad prognosis, leading them to conclude that EIF4G1 could be a novel potential target for therapeutic interventions [29]. Based on mRNA expression data for EIF4G1 from TCGA datasets, they analyzed the survival of patients with different cancer, including mesothelioma.…”
Section: Discussionsupporting
confidence: 93%
“…3 (VI)] comes from a study of the effects of knockdown of the gene family of eukaryotic translation initiation factors (EIF) by RNAi in MCF10A cells. EIF3b is a promising prognostic biomarker and a potential therapeutic target for patients with clear cell renal cell carcinoma 32 , and EIF4GI is a target for cancer therapeutics 33 .…”
Section: Resultsmentioning
confidence: 99%
“…IHC analysis was performed using a rabbit polyclonal SYT13 antibody (OAAB02896; Aviva Systems Biology, San Diego, CA, USA) to analyze 40 sections from patients with pT4a gastric cancer, as previously described. 37 External validation cohorts were generated using global cohort data obtained from TCGA Research Network via the open source cBioPortal ( https://www.cbioportal.org/ ) 38 and the Kaplan-Meier Plotter ( http://kmplot.com/analysis/ ). 39 …”
Section: Methodsmentioning
confidence: 99%